Arahan Penataan Guna Lahan Dalam Upaya Menjaga Keselamatan Operasi Penerbangan - supartika, nina; soma, Soekmana; Prasetyo, irwan (Journal of Urban and Regional Development Studies, 2023)
The growth of air transportation in the city of Bandung is quite high. The importance of air transportation services is threatened by the disruption of inappropriate land use and this has a big impact on the safety of the airport and the community around the airport. This research aims to answer problems related to violations of requirements for using land, water or air in the flight operations safety area of Husein Sastranegara Airport. This research uses a descriptive approach method. The analysis used is land use pattern analysis, Spatial Planning policy analysis, and requirements analysis for using land, water or air in flight operations safety areas. Based on the results of a study of land use patterns in the area around the safe flight operations of Husein Sastranegara Airport, there is a mismatch in space use with the typology of space use incompatibility from local protected areas, housing, public service facilities, defense & security to industry, and natural protected areas to religious services and government offices. From the study of the four variable requirements for using land, water or air in the flight operations safety area of Husein Sastranegara Airport, it shows that these four variables are no longer fulfilled.